BIOMARKERS TO IDENTIFY THE PATHOLOGICAL BASIS FOR FRONTOTEMPORAL LOBAR DEGENERATION - Grossman, Murray (2011)
Recent findings assessing the utility of biomarkers are reviewed that help identify the basis for disease in patients with frontotemporal lobar degeneration (FTLD) spectrum pathology. Biofluid studies identify about 15% of patients with FTLD due to a genetic mutation that is associated with the specific histopathologic features of TDP-43 or a tauopathy. Other genetically-based risk factors and targeted proteomic searches of plasma and cerebrospinal fluid have suggested additional markers that may be useful in sporadic cases of FTLD. While progress has been made in developing biomarkers for FTLD, additional work is needed to extend these advances so that the histopathologic abnormality causing FTLD can be specified in an individual patient.